2016
DOI: 10.1111/ger.12229
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation into patients' perspectives on edentulousness

Abstract: This study illustrates that some elder edentate patients were dissatisfied with the functionality of their dentures and raised concerns that about the quality of dentures which may be provided to them by dentists. These participants identified clinical dental technicians as a preferred point of contact for their care. Consideration should be given to new oral healthcare delivery models which are accessible and acceptable to future elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…This perception can manifest previous negative or frustrating experiences or the disbelief of individuals in conservative dental practice. As already observed, 32 the participants like not having to consult the dentist anymore since with extractions, the problems would be solved in a single visit, thus being free of “engine noise” and “needles.”…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This perception can manifest previous negative or frustrating experiences or the disbelief of individuals in conservative dental practice. As already observed, 32 the participants like not having to consult the dentist anymore since with extractions, the problems would be solved in a single visit, thus being free of “engine noise” and “needles.”…”
Section: Resultsmentioning
confidence: 94%
“…This result showed that subjects presented resilience and adaptability to cope with a disability resulting from reduced oral function. 32 The resolving of problems caused by the use of the dentures showed that acceptance in the face of difficulties was also linked to religious beliefs since resorting to God contributed to the solution. In a previous study among Saudis, it was concluded that spiritual belief could significantly soften the impact of serious life events.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen articles were aimed at assessing patients' views on dental implants. The subject areas (Table 4) included patients feelings about losing teeth (Meaney et al, 2017;Parahoo et al, 2019), their experiences with impaired function following tooth loss (Lantto & Wardh, 2013), what their wishes and demands were from dental implant management (Abrahamsson et al, 2017;Atieh et al, 2016;Boeskov Ozhayat et al, 2019;Cronin et al, 2009;Grey et al, 2013;Johannsen et al, 2012;Kashbour et al, 2017Kashbour et al, , 2018aKashbour et al, , 2018bNarby et al, 2012), their engagement with private implant treatment (Exley et al, 2012), changes in their quality of life following implant treatment (Gatten et al, 2011;Hyland et al, 2009; T. E. Nogueira, et al, 2019;R. B. Osman et al, 2014;Rousseau et al, 2014), and why some elderly patients declined dental implant treatment even if it was available (Ellis et al, 2011).…”
Section: Reported Research Aimsmentioning
confidence: 99%
“…Another study investigated the educational value of YouTube patient testimonials (Ho et al, 2017). (Kashbour et al, 2018a(Kashbour et al, , 2018bLantto & Wardh, 2013;Meaney et al, 2017). One of them did not mention ethical approval (Ho et al, 2017), but the research was a document analysis of YouTube patient testimonial videos which appeared to be exempted from ethical approval.…”
Section: Reported Research Aimsmentioning
confidence: 99%
“…Qualitative research methods permit the documentation of patient experiences of oral health and oral diseases as legitimate studies of enquiry, eg toothache, 18 TMJ 19 dental anxiety, 20 edentulousness 21 and head and neck cancer. 22…”
Section: The Subjective Experience Of Oral Healthmentioning
confidence: 99%